2000
DOI: 10.1080/10715760000300351
|View full text |Cite
|
Sign up to set email alerts
|

The steady-state levels of oxidative DNA damage and of lipid peroxidation (F2-isoprostanes) are not correlated in healthy human subjects

Abstract: Oxidative damage to DNA in human tissues can be determined by measuring multiple products of oxidative damage to the purine and pyrimidine bases using gas chromatography-mass spectrometry (GC-MS). Oxidative damage to lipids (lipid peroxidation) can be quantitated by the mass spectrometry-based determination of F2-isoprostanes, specific end-products of the peroxidation of arachidonic acid residues in lipids. For both DNA base damage products and 8-epi prostaglandin F2alpha (PGF2alpha), there is a wide variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
3
15
0
1
Order By: Relevance
“…All of these factors could contribute to DNA damage with serious consequences for kidney disease progression [17]. The degree of oxidative DNA damage varies wildly between individuals, no matter how it is measured [37][38][39][40][41][42]. It seems likely that both dietary and genetic influences are responsible [3].…”
Section: Discussionmentioning
confidence: 96%
“…All of these factors could contribute to DNA damage with serious consequences for kidney disease progression [17]. The degree of oxidative DNA damage varies wildly between individuals, no matter how it is measured [37][38][39][40][41][42]. It seems likely that both dietary and genetic influences are responsible [3].…”
Section: Discussionmentioning
confidence: 96%
“…However, there is no previous study focusing on oxidative DNA damage in BD, and to our knowledge, the present study is the first in which In the literature, the relationship between oxidationinduced lipid peroxidation and DNA damage is controversial. While some reports suggest that under oxidative stress, lipid peroxidation mediates DNA damage [34], other reports claim that these are independent events [35]. The present study found a positive correlation between oxidation-induced lipid peroxidation and DNA damage in BD, which might implicate contribution of lipid peroxidation on DNA damage.…”
Section: Discussionmentioning
confidence: 62%
“…Oxidation is a complex process, and unless this can be studied at the site of injury, comparisons between the antioxidant capacity of a compound in vitro and possible health benefits are immensely speculatory. Furthermore, a general lack of correlation between the various in vitro/ex vivo assays and biomarker studies as reported in the literature contribute to inconsistencies in the interpretation of results [35][36][37]. For these reasons, more direct measures of oxidative response must be explored.…”
Section: Understanding Measurements Of Oxidationmentioning
confidence: 99%